681. Induction Immunosuppression Selection in People Living with HIV Undergoing Deceased Donor Kidney Transplantation: U.S. National Trends from 2000 to 2018. (31st December 2020) - Cano, Edison J; Mullan, Aidan; Vijayvargiya, Prakhar; Shweta, F N U; Gurram, Pooja; Rizza, Stacey; Mahmood, Maryam; Badley, Andrew; Dean, Patrick; Cummins, Nathan
Abstract: Background: Human Immunodeficiency Virus (HIV) outcomes have significantly improved at the expense of other age-related diseases including chronic kidney disease. Early reports of people living with HIV (PLWH) undergoing deceased-donor kidney transplantation (DDKT) showed poor outcomes, but these have notably improved after introduction of antiretrovirals. Despite years of experience, the optimal induction immunosuppression (IIS) in PLWH remains subject of debate. Large-scale studies describing the current ISS practices in PLWH undergoing DDKT are lacking. Here, we describe the U.S. national trends of IIS used in PLWH undergoing DDKT from 2000 to 2018 using the United Network of Organ Sharing (UNOS) database. Methods: We analyzed the UNOS database to determine the selection of IIS in PLWH undergoing first-time DDKT between 1/1/2000 and 12/31/2018. Cases with unknown HIV status at the time of transplant were excluded. Age, sex and demographics were analyzed. The regimen used for IIS was compared based on HIV serostatus and the change in induction regimen was trended over time. Results: A total of 139, 650 cases underwent DDKT during the study period. Among these, 1, 384 were identified as HIV-positive. PLWH were significantly younger than HIV-negative (49±10 years vs. 51.6 ± 15.3 years; p< 0.001) (Table 1). A greater proportion of men was seen in the PLWH group compared to HIV-negative persons (76.2% vs. 60.4%; p< 0.0001). In the HIV-negative group, 12.1% undergoing DDKT did not receive IIS compared to 16.4% in PLWH (p< 0.0001). Medications that have significantly increased in use with years in PLWH included rabbit anti-thymocyte globulin (rATG), steroids, and basiliximab (3.54, 3.25, 2.28, respectively; p< 0.001). On our trend analysis (Figure 1), the percentage of PLWH receiving any IIS is increasing by 4.04% each year (p< 0.001). Table 1 Figure 1 Conclusion: Our study suggests that IIS is an increasing practice in PLWH undergoing DDKT, predominantly using rATG, steroids, and basiliximab. Understanding the current practices might lead to further studies to determine the long-term outcomes after different induction regimens in PLWH. Disclosures: All Authors : No reported disclosures